The Impact of Sharia Supervision and Corporate Governance on Earnings Management in Islamic Banks - Nahomy, Aisha (2017)
Islamic values as the underlying principle of Islamic banks are expected to control bank’s management from doing unethical things such as earnings management. This paper aims to investigate the level of earnings management in Islamic and conventional banks. This study also investigates the impact of the board of directors, CEO duality, and sharia supervision to the earnings management within conventional and Islamic banks. Using Islamic and conventional banks in ten most developed Islamic finance countries from 2006-2015, this study found earnings management level in both groups is not significantly different from each other. The existence of Islamic values and Sharia Supervisory Board (SSB) does not make any significant difference in controlling management opportunistic behaviour in Islamic banks. This study also found that several factors such as SSB size, the percentage of SSB interlock, and CEO duality affect earnings management in Islamic banks. Meanwhile, board size influences earnings management in conventional banks positively. Other board characteristics such as board meeting and board independence are not significant to explain earnings management in both groups. The findings of this study highlight the effect of Islamic bank's characteristics to deter earnings management. Additionally, this research contributes to a richer understanding of the effect of SSB interlock phenomenon in the international context. Regulations to limit the maximum number of involvement a sharia scholar in more than one bank should be considered as it will improve the quality of sharia supervision in Islamic banks.